Implementation of The Education Curriculum For ABK - Ringgi Rahmat Fitra; Rochmat Wahab; Hana Andriningrum (Jurnal Ilmiah Sekolah Dasar, 2023)
Regulations on inclusive education explain in more detail about inclusive education as an education delivery system that provides opportunities for all students who have disabilities and have potential intelligence and/or special talents to participate in education and learning in an educational environment together with other students. This study aims to analyses the implementation of educational curriculum for students with special needs. Researchers used a qualitative approach with the case study method which was carried out by observation, research, implementation, data analysis and preparation of research reports. This study involves a principal, 2 teachers and 2 guardians of students with special needs. This study uses data collection techniques including observation, interviews and documentation studies. Data analysis in this study was carried out through stages including data collection, data reduction, data classification, and making conclusions. The results showed that the school is still not optimal in implementing the curriculum for students with special needs at school due to a lack of understanding and the high difficulty of controlling the learning process, especially in the delivering material and assessment section.